D’une eschatologie heurtée par la science-fiction : les genèses clivées du blitz theatre group et du Groupe la Galerie - Yann-Guewen Basset (ReS Futurae)
This article focuses on two recent shows: 6 a.m. How to disappear completely (2015), created by the Athenian collective blitz theatre group (2004–2018) and La Bible, vaste entreprise de colonisation d’une planète habitable (2018), written and directed by Céline Champinot with the company Groupe La Galerie. Through these two caseworks, this article aims to analyze an interweaving of science-fictional and religious elements and its impact on dramaturgy and theatrical aesthetics. Decontextualizing such elements as a specific space-time – the ‘Zone’ invented by Arkady and Boris Strugatsky in their novel Roadside Picnic in 6 a.m. How to disappear completely – or post-human characters – Philip K. Dick’s androids coming from Do Androids Dream of Electric Sheep? in La Bible, vaste entreprise de colonization d’une planète habitable — the two shows seem to create paradoxical and clived aesthetic experience which, at the same time, desecrates the religious plot of their fictions and spiritualizes the SF aspects. Considering this dialectic, this article examines the possible legacy of SF narratives to contemporary scenes – particularly to tragic aesthetics – and it questions the eventuality to integrate these shows into the SF genre.